PENERAPAN HYGIENE DAN SANITASI PADA OLAHAN PANGAN KERIPIK SINGKONG PT. KREASI LUTVI KEC. PANCUR BATU - Rani Suraya; Lutfiah Ramadhani, Mughni Muizza (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2024)
PT Kreasi Lutvi, a company that produces processed cassava chips, implements hygiene and sanitation. However, in one of the previous studies there were still some shortcomings. This study aims to analyze and assess the application of hygiene and sanitation in processed cassava chips at PT Kreasi Lutvi. Using a qualitative approach method of descriptive research type. The research respondents were 5 employees representing each production section. The research discusses the results of various aspects, starting from the selection of raw materials, washing, processing, storage, and packaging of chips which can be concluded to be sufficient to fulfill the application of hygiene and sanitation. However, in some aspects it still needs to be improved again such as production equipment, the use of oil and the application of the use of protective equipment such as gloves for each employee.